Model Peningkatan Customer Satisfaction melalui Product Quality, Quality Service, dan di Mediasi oleh Brand Image (Studi pada Franchise Mie Gacoan di Kabupaten Pati) - Erwin Mandala Putra; Tri Wikaningrum (ARZUSIN, 2026)
Increasingly intense competition in the culinary business, particularly in fast-food restaurants such as Mie Gacoan in Pati City, requires companies to improve customer satisfaction through product quality, service quality, and brand image. This study was motivated by customer complaints regarding service and consumption experiences that had not been optimal. This study aimed to analyze the effect of product quality and service quality on brand image and customer satisfaction at Mie Gacoan in Pati City. This study used a quantitative approach with a survey method through the distribution of questionnaires to Mie Gacoan customers in Pati City. The data were analyzed using Structural Equation Modeling (SEM). The results showed that product quality and service quality had a positive and significant effect on brand image and customer satisfaction. In addition, brand image also had a positive effect on customer satisfaction. The conclusion of this study confirms that consistently improving product and service quality can strengthen brand image and increase customer satisfaction. The implications of this study indicate the importance of companies maintaining consistent product quality, improving service speed and accuracy, and building a strong brand image to maintain customer satisfaction and loyalty. Keywords: Product Quality; Service Quality; Brand Image; Customer Satisfaction; Fast-Food Restaurant